COVID-19 Health Protocol and Religious Activities: Knowledge, Attitude, and Compliance among Generation Z - Indri Ramayanti; Wieke Anggraini; Fatinah Fairuz Qonitah; Ahmad Ghiffari; Thia Prameswarie (HM Publisher, 2021)
Background: COVID-19 (coronavirus disease 2019) is a contagious infection currently affecting people worldwide, including in Indonesia. The spread of this virus is extremely rapid, and the number of deaths continues to rise. Compliance with the health protocol is one method of preventing the spread of COVID-19. The purpose of this study is to determine the relationship between generation-Z (gen-Z) knowledge and attitudes toward the use of masks, keeping distance, and washing hands as a means of preventing COVID-19 in religious activities at houses of worship in Palembang. Method: The observational analytic cross-sectional research design with the study's population consists of generation Z members who participate in religious activities in places of worship. The cluster random sampling method yielded 147 respondents. The data collected are primary data obtained directly from the research subjects via a questionnaire and secondary data obtained from the Palembang City Ministry of Religion. They were using the Pearson chi-square test to analyze descriptive data. Results: According to the findings, 79 people (53.7%) out of 147 respondents have good knowledge, while 75 people have a good attitude (51% ). The results obtained a statistically significant p-value of 0.05, indicating a relationship between gene Z knowledge and attitude and adherence to the use of masks, keeping distance, and washing hands. Conclusion: There is a significant relationship between knowledge and attitudes toward COVID-19 infection prevention in Generation Z who participate in religious activities in Palembang City.